"Real Men Stand for Our Nation": Constructions of an American Nation and Anti-Kaepernick Memes. (August 2021) - Dickerson, Nik; Hodler, Matt
On September 1, 2016, San Francisco 49ers quarterback Colin Kaepernick kneeled for the playing of the national anthem arguing that he was "not going to stand up to show pride in a flag for a country that oppresses black people and people of color, " noting that "this is bigger than football and it would be selfish . . . to look the other way. There are bodies in the street and people getting paid leave and getting away with murder." Kaepernick received a tremendous amount of backlash for this action, and many White fans/media pundits accused him of disrespecting the flag and U.S. military. This act took place during the very contentious presidential election in the United States between eventual winner Donald Trump and Hillary Clinton. During this election, the Trump campaign mobilized discourses of White nationalism, and even employed alt-right member Steve Bannon as Trump's chief advisor for a period. The Trump campaign capitalized on a set of White backlash politics that had been growing since the 1990s, and the reactions to Kaepernick's protest cannot be separated from this larger context. In this article, we critically read internet memes of Colin Kaepernick to gain insight into the relationship between race, gender, and the nation during the rise of Donald Trump to the U.S. presidency.